Analisis Kontrastif Pemarkah Lokatif ‘di’ dalam Bahasa Indonesia dengan ‘ni’ dan ‘de’ dalam Bahasa Jepang - Elizabeth Ika Hesti Aprilia Nindia Rini (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2009)
Understanding the mother tongue is as important as understanding the second language for language learners. Contrastive analysis provides a means to compare and find similarities and differences between the two languages so that the exchange f meaning can be done with accuracy. The word “di”, “ni”, and “de” have the same function as a locative marker, however, each has distinct uses in the sentence. Kata kunci : Analisis Kontrastif, ‘di’,  Partikel Kasus ‘ni’ dan ‘de